Oral fluid supplementation for the prevention of post-dural puncture headache: A noninferiority randomized controlled trial - Emmanuelle Cartron; Christelle Volteau; Maxime Leroy; Annastasia Voisine; Jérôme Emmanuel Dauvergne; Céline Ballet; Jean-Philippe Talarmin; Marie-Annick Quéau; Marylène Catinault; Emmanuelle Gazeau; Carole Haubertin; Romain Charreau; et al. (PLoS ONE, 2025)
Aim(s) To investigate the impact of the absence of specific advice for oral fluid intake, compared to supplementation water intake on the occurrence of post-dural puncture headache. Design A prospective, open-label, non-inferiority, multicenter trial including hospitalized patients requiring a diagnostic lumbar puncture in seven hospitals in France. Methods Patients were randomly allocated (1:1) either to receive no specific advice on oral fluid intake (FREE-FLUID), or to be encouraged to drink 2 liters of water (CONTROL) within the 2 hours after lumbar puncture. The primary outcome was the post-dural puncture headache rate within the 5 days after lumbar puncture, with a non-inferiority margin of 10%. The secondary outcome was the time-to-post-dural puncture headache onset between Day 0 and Day 5. Results From November 2016 and July 2019, we have included 554 participants. The primary outcomes occurs in 33.1% patients in the FREE-FLUID group, versus 38.0% in the CONTROL group with adjusted difference of 3.7%. Conclusion Among patients who had lumbar puncture, our study shows the noninferiority of the absence of specific advice on water intake after a lumbar puncture, compared with advice to increase oral fluid to prevent a post-dural puncture headache. Impact The value of questioning the appropriateness of non-evidence-based nursing care may allow time to be devoted to more relational and comforting care. Reporting method The study adheres to the CONSORT reporting guidelines. Patient or public contribution No patient or public contribution. Trial Registration Clinical Trials.gov (NCT02859233, August 9, 2016).